Influence of Quizizz Aplication as Quantum Learning Model Toward the Concept of Understanding Mathematics Ability - Hilma Arini Millati (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
One of the external factors that influenced the concept of understanding ability is the learning style that used in the classroom activities. The aim of this research is to investigate whether Quizizz application as the Quantum learning model influence or not for the concept of understanding ability at grade XI senior high school NU 1 Kemranjen. The purpose of this study is to find out whether there is influence and implementation on the application of the Quantum Learning model assisted by the Quiz application on the ability to understand the concept of class XI SMA Ma'arif Nu 1 Kemranjen. This research used an Experiment as a method of this and Quantitative as the approach. The population of this research is all students of grade XI senior high school which consist of 166 students. The class of XI IPA which consist of 27 students as the control class and XI IPA 2 which consist of 28 as the experiment class. The result showed that there was influence and implementation using Quizizz application as the Quantum Learning model. Meanwhile, the instrument of post-test in control class and experiment class which using independent sample test achieved sig = 0,000 < α = 0,05 that revealed different average significant, as a result, there is influence using Quizizz application as Quantum Learning model in the concept of understanding ability of grade XI senior high school NU Kemranjen.